Design of a reconfigurable front‐end for a multistandard receiver for the frequency range of 800 MHz to 2.5 GHz. (20th May 2018) - Zare Fatin, G.; Koozehkanani, Z.D.; Fotowat‐Ahmady, Ali; Sobhi, Jafar; Farrell, Ronan
Summary: In this paper, a reconfigurable receiver front‐end for the frequency range of 800 MHz to 2.5 GHz is presented. The radio frequency front‐end is realized in wideband form with reconfigurable baseband filter. The proposed front‐end targets the GSM, WLAN, WCDMA, and GPS standards residing in the aimed frequency range. The necessary specifications for each individual standard have been revisited and recalculated. The interaction of the different standards and their interoperability has been thoroughly investigated and extra specifications derived for the multistandard receiver. The multistandard receiver has been designed, layouted, and simulated in RFCMOS 0.18‐μm process. Abstract : The architecture of the proposed front‐end.